Effects of Malaria in pregnancy on newborn anthropometry - Catherine Olufunke Falade; Olukemi O Tongo; Oluwatoyin O Ogunkunle; Adebola Emmanuel Orimadegun (Journal of Infection in Developing Countries)
Background: Malaria in pregnancy remains a major cause of infant mortality through its contribution to preterm delivery, low birth weight and intrauterine death.